Soft Story Design of Reinforced Concrete Structures with Masonry Infill Walls - Seyed Mojtaba Hosseini Gelekolai; Mohammad Reza Tabeshpour (Journal of Rehabilitation in Civil Engineering)
Based on the seismic design codes to prevent soft-story failure, columns of a soft story must be designed for amplified loads due to the discontinuity of braces or shear walls in that story. Because of the masonry infill walls discontinuity, Soft story failure has been reported in the recent earthquakes. Most national seismic design codes don't consider the effect of masonry infill walls for the design of the soft story. This paper aims to investigate the soft story failure and then present a simple formula for the design of soft-story in moment resisting frame structures. In this paper, the different arrangements of masonry infill walls are considered. Structural modeling was carried out based on reliable parameters and some national or international seismic design codes. By using nonlinear static analysis, a simple methodology is proposed and the main result is a simple formula that can be used for the engineering design of concrete moment resistant frames.